Non-Performing Loan Market Assessment in Pakistan : Developing a Secondary NPL Market - Diagnostic Assessment Report - International Finance Corporation; World Bank (International Finance Corporation: Washington, DC, 2022)
The objective of this Non-Performing Loan (NPL) Market assessment diagnostic report is to examine and assess the NPL market in Pakistan, and identify bottlenecks and practical areas that could be addressed in the short and medium term to make the NPL market in Pakistan more investor friendly. The report analyzes and sizes the NPL market in Pakistan and identifies key financial trends, NPL concentrations, major participants, sectors, and segments. It presents the current state of Pakistan’s NPL market, identifying the legal, prudential, taxation, and other regulatory and practical impediments for financial institutions and potential NPL investors to create and operate a viable secondary market for NPLs. The report also assesses the feasibility of potential secondary market transaction models for NPLs within the context of the current laws and regulations in Pakistan.